Data resource profile: understanding the patterns and determinants of health in South Asians-the South Asia Biobank - Song, P.; Gupta, A.; Goon, I.Y.; Hasan, M.; Mahmood, S.; Pradeepa, R.; Siddiqui, S.; Frost, G.S.; Kusuma, D.; Miraldo, M.; Sassi, F.; Wareham, N.J.; et al. (Oxford University Press., 2021)
No abstract available
Indexed in MEDLINE
Keywords: South Asia Biobank